Single Nucleotide Polymorphisms in Apolipoprotein B, Apolipoprotein E, and Methylenetetrahydrofolate Reductase Are Associated With Serum Lipid Levels in Northern Chilean Subjects. A Pilot Study - Gálvez, Anita S.; Ramírez, Hugo; Placencia, Pablo; Rojas, Claudio; Urzúa, Ximena; Kalergis, Alexis M.; Salazar, Luis A.; Escobar-Vera, Jorge (Frontiers in Genetics, 2021)
Characterization of allelic variants is relevant to demonstrate associations among genetic background and susceptibility to develop cardiovascular diseases, which are the main cause of death in Chile. Association of APOB, APOE, and MTHFR polymorphisms with higher lipid levels and the risk of developing hypertension and cardiovascular diseases have been described. Thus, the aim of this study was to assess genotype distribution and relative allelic frequency of ApoB rs693, ApoE rs7412, ApoE rs429358, MTHFR rs1801131, and MTHFR rs1801133 allelic variants and their effects on lipid profile in young healthy men and women from Northern Chile. A group of 193 healthy subjects were enrolled for this study. Genotyping of rs693 (APOB), rs7412 and rs429358 (APOE), and rs1801131 and rs1801133 (MTHFR) polymorphisms were performed by real time PCR. In addition, lipid profiles were determined and associated to genetic data. The genotype distribution was APOB rs693 (CC = 37%, CT = 41%, and TT = 22%), APOE rs7412/rs429358 (E4 = 0.06, E3 = 0.91, and E2 = 0.03), MTHFR rs1801131 (AA = 57%, AC = 30%, and CC = 13%), and MTHFR rs1801133 (CC = 20%, CT = 47%, and TT = 33%). The association of the genetic variants with plasma lipid levels showed that women, but not men, carrying APOB mutated allele (T) and Apo E4 allele presented lower values of total cholesterol when compared with C/C homozygous genotype or E3 allele, respectively (p < 0.05). In addition, a subgroup analysis revealed that ApoB C/C homozygous women exhibited higher values of HDL-C when compared with men carrying identical genotype (p < 0.01). On the other hand, women carrying E4 allele exhibited lower values of triglycerides when compared with male carrying identical genotype (p < 0.05). Finally, women carrying mutate allele (C) for MTHFR rs1801131 showed lower levels of triglycerides when compared with A/A homozygous genotype (p < 0.05) and lower levels of LDL-C for MTHFR rs1801133 in females carrying (T) allele when compared with males carrying identical genotype (p < 0.05). In summary, the present data showed that APOB, APOE, and MTHFR single nucleotide polymorphisms are associated to lipid levels in a gender-dependent manner among healthy subjects from Northern Chile, especially in women.